2012
DOI: 10.1007/s00268-012-1674-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Ultrasonography Assessment of Vocal Cord Movement During Thyroid and Parathyroid Surgery

Abstract: Surgeon-performed US appears to be a relatively accurate method for assessing vocal cord movement in the preoperative setting. It can be used to select patients to undergo laryngoscopic examination before thyroidectomy and parathyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 51 publications
1
81
1
1
Order By: Relevance
“…13,14 Many groups are evaluating the efficacy of less invasive means of screening for vocal cord dysfunction before and after thyroid surgery, including voice questionnaires and ultrasonographic evaluation of cord function. 13,[15][16][17][18] The majority of thyroid surgeons likely either lack time or choose not to use formal voice assessment methods preoperatively. We are strong proponents of surgeon-performed, in-office ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Many groups are evaluating the efficacy of less invasive means of screening for vocal cord dysfunction before and after thyroid surgery, including voice questionnaires and ultrasonographic evaluation of cord function. 13,[15][16][17][18] The majority of thyroid surgeons likely either lack time or choose not to use formal voice assessment methods preoperatively. We are strong proponents of surgeon-performed, in-office ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Transcutaneous laryngeal ultrasonography (TLUSG) has been a good, noninvasive selective tool for laryngoscopic examination. 10,11 Our recent study found the overall accuracy of diagnosing VCP using TLUSG in the preoperative and postoperative settings were #100.0% and #94.6%, respectively 12 ; therefore, TLUSG was recommended to be a screening tool for VCP in the preoperative and postoperative assessments. [10][11][12] However, TLUSG remains a relative new and evolving imaging technique in VC assessment.…”
mentioning
confidence: 97%
“…[1][2][3][4] Recently, the utility of transcutaneous laryngeal ultrasonography (LUS) has been investigated as an alternative to the gold standard direct laryngoscopy (DL), which can be associated with patient discomfort, inconvenience, and additional cost. [5][6][7][8] The previously described midline-, or anterior-approach LUS, however, has significant limitations as a diagnostic tool because of its high failure rate of VC visualization in patients with prominent or calcified thyroid cartilage, typically observed in elderly or male patients. 5,9 Wong et al 9 reported that the older age and male sex were found to be independent risk factors for ''unassessable'' VC.…”
mentioning
confidence: 98%